Separation and Micro Determination of Zinc(II) and Cadmium(II) in Food Samples Using Cloud Point Extraction method - Abd Wannas, Fatimah; Azooz, Ebaa Adnan; Ridha, Rana Kadhim; Jawad, Shawket Kadhim (Iraqi Journal of Science, 2023)
The cloud point extraction technique has become increasingly popular in recent years for trace metal separation and preconcentration. When heated to a specific temperature, cloud point extraction utilizes the property of nonionic surfactants in aqueous solutions to generate micelles and become turbid (so-called cloud point temperature). For analytical chemists, developing a simple and selective technology for the separation and determination of metals and medicinal drugs is a critical concern. Therefore, a sensitive, accurate, and green cloud point extraction (CPE) procedure was developed for the micro-determination of metal cations like zinc (II) and cadmium (II) in food samples. Triton X–114 and 1-(4-(Phenyldiazenyl) phenyl) azo naphthalene-2-ol (Sudan III) were used as extractants. Sudan III forms an ion-pair association complex with metal ions when the pH is 9. In the presence of 5 ppm zinc (II) or 4 ppm cadmium (II) in an aqueous solution, the maximum extraction efficiency should be achieved. In order to create Cloud Point Temperature (CPT) quantitatively, the extraction applications in this approach required heating at 85°C for 20 minutes. In this work, the impacts of different surfactants, pH, stoichiometry, and various organic reagents on interferences as well as spectrophotometric determination were explored. The linearity ranges of zinc (II) and cadmium (II) were 0.25-700 and 0.25-400 ppm, respectively. The results show low detection limits of 0.035 and 0.042 ppm for zinc (II) and cadmium (II), respectively. Also, the quantification limits for zinc (II) and cadmium (II) are 0.116 and 0.140 ppm, respectively.